Studi Kelayakan Usaha Media Sosial Tiktok Tentang Promosi Kesehatan Gigi dan Mulut - Fazriah, Siti Halimah; Laut , Deru Marah; Chaerudin, Denden Ridwan; Ningrum, Nining; Handayani, Ratna Dwi (Poltekkes Kemenkes Bandung, 2024)
A business feasibility study is research and evaluation of whether a project can be profitable or not. This evaluation begins by assessing the investment to be used, and the results are recorded in a written report. The report from this feasibility study can be used as a guide or tool to gauge the extent to which the investment has been made. Feasibility studies can be seen from two aspects, namely financial and non-financial. Health Promotion efforts are made to convey information about Health to the public, with the aim that they can get a healthy life. The purpose of this study is to find out the feasibility of tiktok media business in the field of dental and oral health promotion. The method used is descriptive research with a qualitative approach Triangulation which is carried out by comparing information or data through interviews, observations and research. The results of this study show that conducting dental and oral health promotion efforts through Tiktok social media is declared feasible based on 5 aspects of feasibility studies. Evaluation of this research that promotion of dental and oral health is feasible.